Analytical Study Of the Relationship of the Labor Market to the Problem of Unemployment in Algeria - Belarbi Abdelkader (Indonesian Journal Of Business And Economics, 2019)
In recent years, the Algerian labor market has undergone drastic changes as a result of supply and demand shocks caused by a drop in unemployment rates from 17.7% in 2003 to 11.7% in 2018 according to (ONS) data. However, this decline was more quantitative than qualitative, Under the age of 30, with a ratio of 60% among the new job seekers.In this paper, we will attempt to analyze the trends of the labor market and its ability to absorb youth unemployment through the field study carried out at the Tlemcen State level in 2017 to study the causal relationship between social and economic variables related to the development of labor resources, Linear approach based on the Statistic program.